A study of the neuroprotective role of Punica granatum and rosuvastatin in scopolamine induced cognitive deficit in rats - Fatima, Fariha; Rizvi, Dilshad A.; Abidi, Afroz; Ahmad, Ali; Shukla, Pooja; Qadeer, Fardan; Srivastava, Karan (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The present work has been planned to find out the effect of Punica granatum and Rosuvastatin on learning and memory in Scopolamine induced cognitive deficits in rats. Scopolamine being an anticholinergic agent is used fervently in experimental models for memory deficits and has been widely implicated for the screening of cognitive dysfunction. Punica granatum (Pomegranate) has shown to suppress tumor neuronal cells, hence it can be a potential agent in providing neuroprotection for preventing the development and progression of AD. There are conflicting reports indicating the role of statins as a neuroprotective agent. This contradiction led us to investigate the effect of the role of Rosuvastatin on memory. The test agents were further compared to the standard treatment group acetylcholinesterase inhibitor i.e. Donepezil. Methods: Male wistar rats 150-200gms were divided into 4 groups of 6 rats each. Amnesia was induced by scopolamine 3mg/kg ip at day 5 in all the groups. Group1 (amnesic control) given distilled water; group 2(standard treatment i.e. Donepezil 0.5mg/kg orally); group 3(Rosuvastatin group10mg/kg orally); group 4 (Punica granatum juice 500mg/kg orally) The methods for validating cognition deficits were behavioural tests like Cook’s pole response and Passive Avoidance response. Results: It was evident from our research that the Punica granatum juice and Rosuvastatin effectively antagonized the scopolamine induced cognitive impairment in the paradigms studied. The neuroprotective effect of Punica granatum juice was better as compared to the Rosuvastatin group and the effects of the former were comparable with the standard treatment i.e. Donepezil group. Conclusions: Punica granatum has a remarkable protective role in memory function, learning, cognition and behavior in Scopolamine induced amnesia model of Alzheimer’s disease which was better than Rosuvastatin treatment.